Republic of Mozambique : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
The Poverty Reduction Strategy Papers (PRSPs) on the Republic of Mozambique review the country's macroeconomic, structural, and social policies in support of growth and poverty reduction, and external financing needs and major sources of financing. It is essential to guarantee that mechanisms of democratization are present within the political parties and to develop participative democracy. Monitoring and evaluation is also a means of keeping abreast of not only the government, but also organizations in civil society, the Mozambican legislature, and the cooperation partners.